Analysis of turnover intention and influencing factors among female nurses with two children in Grade A tertiary public hospitals in Sichuan province: a cross-sectional study - Ling, Chengrong; Tao, Liande; Wang, Xin; Wu, Yunlian; Chai, Yong; Zhang, Lan (Frontiers in Public Health, 2024)
Objective: This study aims to examine the current status of turnover intention among female nurses with two children and explore the factors influencing their decision to resign, ultimately providing a basis for reducing nurses' turnover intention and stabilizing the nursing workforce. Methods: A convenience sampling method was used to select 1370 in-service female nurses with two children from 65 Grade A tertiary public hospitals in Sichuan Province from September to December 2023. Data was collected through a General Information Questionnaire, Work-Family Behavioral Role Conflict Scale, Regulatory Emotional Self-Efficacy, and Turnover intention Scale.Results: This study revealed that the average score for turnover intention among female nurses with two children was (13.11±3.93). There was a positive correlation between work-family behavioral role conflict and turnover intention (r=0.485, P<0.01), while regulatory emotional self-efficacy showed a negative correlation with turnover intention (r=-0.382, P<0.01). The main influencing factors for resignation among these nurses included age, number of night shifts per month, average monthly income, primary caregiver for children, work-to-family conflict and family-to-work conflict, and the ability to express positive emotions (POS), the capacity to regulate negative emotions such as despondency/distress (DES), and the skill to manage anger/irritation (ANG). Collectively, these factors explained 29.5% of the total variance in turnover intention scores. Conclusions: Turnover intention among female nurses with two children is relatively high. To address this issue, hospital managers shall implement effective measures through various channels to settle work-family conflict, enhance nurses' regulatory emotional self-efficacy, and reduce turnover intention resulting from work-family conflict. Together, these efforts will reduce nurse turnover and foster a stable nursing workforce.